Surveillance Behavior of Juvenile by using RFID and CCTV Monitoring - Apatcha Sirichai; Oranutda Chinnasri; Warrachai Wiriyaromp; Yusaku Fujii; Preecha P. Yupapin (My University, 2011)
This report presents the use of modern communications technology to track the behavior of the Juvenile, which are difficult to track (record) because the number and distance. Network of RFID and GPS is recommended to cover such problems. The system will consolidate and submit to the control center using GPS to check very closely with the Juvenile that route and duration of a safe place will help prevention and suppression of the offender's Juvenile is also possible to detect and recognize.
Keywords: IoT and GPS-based Vehicle Safety Systems